Engagement of Teachers Community in Strengthening Pedagogical Competence Through Technology-Integrated Contextual Teaching and Learning - Susilawati, Wati; Sholihah, Wildatus (ASEAN Journal of Community Engagement, 2025)
This study examines the engagement process of mathematics teachers in improving their pedagogical competence by integrating technology into contextual learning. The integration of technology into the contextual teaching and learning (CTL) approach offers significant opportunities to enhance teacher professionalism. Studies of CTL have shown that such an approach enriches pedagogical competence, strengthens content mastery, and encourages teachers to adapt to digital innovations, develop reflective and analytical practices, and pursue continuous improvement in mathematics teaching. However, many teachers still experience gaps in this technology, particularly in digital literacy, resistance to change, and limited access to adequate facilities and training. This study engaged a community of senior high school mathematics teachers in Bandung, Indonesia, and 56 participants joined the project. The project involved the design and implementation of a digital technology training program to develop learning materials, including teaching modules, electronic learning resources, electronic worksheets (kinesthetic, visual, and auditory), activities for solving non-routine mathematics problems, peer-teaching simulations, and reflective practice. Based on questionnaire, interview, and documentation results, the findings indicate a significant improvement in CTL-based mathematics instruction through technology integration. The evaluation criteria were rated as very good, particularly in the use of AI, AR, ThingLink, and GeoGebra. As a result, this community engagement initiative facilitated the effective implementation of technology-based CTL in enhancing the quality of classroom interaction, conceptual presentation, and student learning motivation, while simultaneously strengthening teachers’ professionalism and their ability to evaluate and refine their teaching practice.